In vitro comparison of the marginal adaptation of cold ceramic sealer with the single-cone obturation technique versus AH-26 sealer with the lateral compaction technique in single-canal teeth - Jalil Modaresi; Fatemeh Mokhtari; Elahe Khodarahmi (BMC Oral Health)
Abstract Objectives This study aimed to compare the marginal adaptation of a cold ceramic (CC) sealer with the single-cone obturation technique with that of an AH-26 sealer with the lateral compaction technique in single-canal teeth. Materials and methods In this in vitro experimental study, the root canals of 24 extracted single-rooted single-canal teeth were instrumented to F3 files by the crown-down technique and randomly assigned to 2 groups (n = 12). The root canals were obturated with a CC sealer and single-cone obturation technique with 4% gutta-percha in group 1 and with an AH-26 sealer and lateral compaction technique with 2% gutta-percha in group 2. After 4 weeks of storage at room temperature and 100% humidity, the root ends were sectioned horizontally 3 mm from the apex, and the mean linear distance between the root filling material and the root dentinal wall was measured under a scanning electron microscope (SEM). Comparisons were made by the Mann‒Whitney test (alpha = 0.05). Results The mean linear distance (gap) was significantly smaller in the CC sealer/single-cone group than the AH-26/lateral compaction group (6.72 ± 2.57 vs. 12.94 ± 4.82 μm, P = 0.001). Conclusion Marginal adaptation was significantly higher with the CC sealer and single-cone obturation technique than with the AH-26/lateral compaction technique, suggesting the suitability of the CC sealer and single-cone obturation technique for a hermetic seal in single-canal teeth.